Effectiveness of an Education Program on Nurses knowledge concerning in Nursing Management for patients with Third degree and bundle branch block in Kirkuk Teaching Hospitals - Abid Salih Kumait AL-Jumaily; Khalidah Mohammed Khudur (College of Nursing,University of Mosul, 2019)
Background and Objectives: Heart block is a disease or acquired condition that causes a fault within the heart's natural pacemaker due to some kind of obstruction (or "block") in the electrical conduction system of the heart.Nurses play an important role in maintaining the health and well-being of patients. Aims of the study was to assess the effectiveness of nursing education program on nursing knowledge concerning in nursing management toward third degree and bundle branch block in Kirkuk's teaching hospitals and to identifying the relationship between the nurses' knowledge and their demographic characteristics such as ( age ,gender and education level) Material and Method :A descriptive study design (quasi experimental study )was carried out at Azadi teaching hospital and Kirkuk general hospital in Kirkuk city for nursing staff who worked at CCU ,RCU unit , emergency unit and internal medicine unit ,from February up to May, 2018. A non - probability (purposive) sample was selected and composed of (80) Nurses (male and female) .Nurses was divided into two groups, study group consisted of (40) nurses exposed to the nursing educational program and control group consisted of (40) nurses were not exposed to the program from Azadi Teaching Hospital and Kirkuk General Hospital in Kirkuk city. The program and instruments were constructed by the researcher for the purpose of the study .The questionnaire was constructed for the purpose of the study which consisted of three parts: the first part include the demographic data (5 ) items (age, gender,residencr , Educational achievement and marital status.The second about training in cardiac care (2) items ( work place and name of training in cardiac care . The third part consist from (18 ) items of general knowledge toward management of third degree of heart block and bundle branch block of heart block. The (SPSS) ver. (22.0) was used for data analysis. Mean, SD, and ANCOVA test, compare means were used to analyze the collected data. Level of significance was the threshold at p<0.05 Results: There were 40 nurses included in the study. Relative to "Gender" 23(57.5%) from sample were female are more illustrated, since, also the study shows the high percent of nursese were at age between (20-39 years) and constitute 35(87.5%) and most of "Age Groups", are focused at the first two groups since .(72.5% ) .Also the results shows (65.0%) were female. With regard to residence Mosul Journal of Nursing, Vol.7, No.1, 2019 - 8 - 28(70.0%) were living in urban areas, The study findings indicated that there were highly significant differences between pre and post tests in the study group in overall main domains related to nurses' knowldg abou management of third degree heart block and bundle branch block Conclusion: The study concluded that the effectiveness of educational program regarding nurses' nurses' knowldg abou management of third degree heart block and bundle branch block . Keywords: Education Program , nursing management, Heart Block